KAJIAN DAYA DUKUNG RUANG TERBUKA HIJAU TERHADAP KINERJA GEDUNG KAMPUS KONSERVASI - Prihanto, Teguh (Semarang State University, 2011)
The aims of this research are: (1) to review the application of green architecture concept to the design of the campus green open space, (2) to assess the physical carrying capacity of green open spaces of the existence of campus buildings and surrounding environment as a conservation area ;(3) to provide open space design recommendations green campus, if not in harmony with the concept of green architecture and do not have a strong bearing on the campus buildings and environment conservation.This research takes place in the region Unnes Campus Faculty of Engineering. In particular review the open spaces that have a direct relationship with the building Building E1 and E2, they are: vehicle parking, sitting groups, parks and forests campus. This was a